Cavity Jahn-Teller polaritons in molecules - Nandipati, Krishna Reddy; Vendrell, Oriol (Physical review, 2023)
Jahn-Teller (JT) polaritons emerge when the two perpendicular, normal-incidence electromagnetic modes of a Fabry-Perot cavity interact with JT active systems. These JT polaritons are characterized by a mixed (+/−)-circular electromagnetic polarization mediated by the molecular JT vibronic coupling of the material subsystem. Consequently, the exchange of photonic and vibronic angular momenta can be very efficient. Due to the photonic-vibronic coupling, the magnitude and direction of the cavity polarization varies for different eigenstates of the cavity-molecule system. This type of light-matter coupling results in polarization inverted states in the polaritonic system—states that can be reached resonantly with either right or left circularly polarized light but which are characterized by a cavity-photon polarization opposite to the external fields used to excite the system.
Gesehen am 17.08.2023